Analisis Kinerja Keuangan Berdasarkan Rasio Profitabilitas Pada PT Air Asia Indonesia Tbk. Antara Sebelum dan Sesudah Go Public Selama Periode 2017 - 2019 - Adipura Danang Maulana (Jurnal Manajemen Dirgantara, 2020)
The purpose of the study is to analyze the financial performance of PT. Air Asia Indonesia Tbk before and after Go Public during the period of 2017 – 2019. The analysis of the financial performance was conducted using the Profitability ratio. The ratio was calculated from the financial reports that have been published by the company in one years before and after the Go Public. The result of the study can be concluded that one years after Go Public.the financial performance showed a growth compared to the financial performance 2 years before Go Public Return on Assets,Return On Equity, Gross Profit Margin, Nett Profit Margin, showed good values after Go Public.